The Effect Of PGPR Biostimulant Concentration and Phosphorus Dosage on the Growth and Yield of Black Soybean (Glycine max (L.) Merril): Pengaruh Konsentrasi Biostimulan PGPR Dan Dosis Fosfor Terhadap Pertumbuhan Dan Hasil Tanaman Kedelai Hitam (Glycine Max (L.) Merril) - Tyas, Nurlaili Trianing; Fitriani, Dwi; Podesta, Fiana; Usman; Suryadi (Universitas Muhammadiyah Sidoarjo, 2025)
Abstract. This study aimed to investigate: (1) the interaction effect between PGPR biostimulant concentrations and phosphorus dosages on the growth and yield of black soybean (Glycine max (L.) Merril), (2) the individual effect of PGPR biostimulant concentration, and (3) the individual effect of phosphorus dosage on the growth and yield of black soybean. The research was conducted in Bentiring from November to March 2025. A factorial Completely Randomized Design (CRD) was employed, consisting of two factors. The first factor was the concentration of PGPR biostimulant (B), which included: B0 = control, B1= 10 ml/L, B2 = 20 ml/L, and B3 = 30 ml/L. The second factor was the phosphorus dosage using TSP fertilizer (P), consisting of: P0 = control, P1 = 125 kg/ha, P2 = 175 kg/ha, P3 = 225 kg/ha. These combinations resulted in 16 treatment combinations, each replicated thee times, yielding a total of 48 experimental units. The interaction between PGPR biostimulant concentration and phodphorus dosage had a highly significan effect on the number of root nodules. The PGPR biostimulant concentration had a highly significant effect on the weight of 100 seeds, fresh root weight, and dry root weight, as well as a significant effect on the number of root nodules. The phosphorus dosage significant affected the number of root nodules and had asignificant effect on plant height at 28 days after planting, number of leaves at 28 days after planting, and harvest time.